2021
DOI: 10.1002/jbm4.10444
|View full text |Cite
|
Sign up to set email alerts
|

A Statistical Approach Regarding the Diagnosis of Osteoporosis and Osteopenia From DXA: Are We Underdiagnosing Osteoporosis?

Abstract: This article has been accepted for publication and undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process which may lead to differences between this version and the Version of Record. Please cite this article as

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 21 publications
(48 reference statements)
1
7
0
Order By: Relevance
“…However, prior studies have shown that the calcaneus is a reasonable bone to use for screening for osteoporosis using ultrasound and quantitative CT [ 18 ]. Prior reports showed that the BMD measurements at different osseous sites were highly correlated [ 27 , 28 ], which would support our finding that the attenuations at different osseous sites are highly correlated. A prior study also showed that the TBS provides complementary information to DXA BMD measurements for prediction of fracture risk [ 29 ].…”
Section: Discussionsupporting
confidence: 91%
“…However, prior studies have shown that the calcaneus is a reasonable bone to use for screening for osteoporosis using ultrasound and quantitative CT [ 18 ]. Prior reports showed that the BMD measurements at different osseous sites were highly correlated [ 27 , 28 ], which would support our finding that the attenuations at different osseous sites are highly correlated. A prior study also showed that the TBS provides complementary information to DXA BMD measurements for prediction of fracture risk [ 29 ].…”
Section: Discussionsupporting
confidence: 91%
“…9,14,17,41,42 The spine and hips may be involved by degenerative changes or bony metastases that may affect the BMD of the bones. 2,[8][9][10]48 Our results show that opportunistic knee CT scans can be used in patients with degenerative changes of the knee.…”
Section: Discussionmentioning
confidence: 99%
“…2 The BMD T-score at the femoral neck is thought to be more reliable because BMD T-scores at the lumbar spine and total hip can be affected by degenerative changes of the spine and hip. 2,8–10…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations